Association of ABCB1 polymorphisms with erlotinib pharmacokinetics and toxicity in Japanese patients with non-small-cell lung cancer. (April 2012) - Hamada, Akinobu; Sasaki, Ji-ichiro; Saeki, Sho; Iwamoto, Norihiro; Inaba, Megumi; Ushijima, Sunao; Urata, Maki; Kishi, Hiroto; Fujii, Shinji; Semba, Hiroshi; Kashiwabara, Kosuke; Tsubata, Yukari; et al.
Aims: We analyzed the association of ABCB1 polymorphisms with erlotinib-induced toxicity and the pharmacokinetics in patients with non-small-cell lung cancer.Materials & methods: After erlotinib 150 mg was administered to 50 patients, ABCB1 polymorphisms were analyzed via either TaqMan ® assays or direct nucleotide sequencing. Plasma concentrations were measured by HPLC.Results: The trough concentration at steady state in patients with the ABCB1 1236TT–2677TT–3435TT genotype was higher compared with others groups (p = 0.021) and patients carrying this genotype had a higher risk of developing higher grade 2 toxicity (p = 0.012).Conclusion: The present study suggested that the ABCB1 1236TT–2677TT–3435TT genotype was associated with higher plasma concentration and the risk of developing higher toxicity in patients treated with erlotinib. Original submitted 5 August 2011; Revision submitted 30 November 2011